Increasing Interest in Reading and Love for the Homeland through Reading Workshops with Indonesian Cultural Content - Hastomo; Supartinah; Dwi Mahmud Rizki Riyanto (Universitas Pendidikan Ganesha, 2025)
Low reading interest and patriotism among students have become critical issues in developing literacy and character from an early age. This study aimed to explore and enhance fourth-grade students’ reading interest and love for their country through the implementation of a reading workshop model based on picture books containing Indonesian cultural values. The research employed a Classroom Action Research (CAR) design. The study subjects consisted of fourth grade students as the primary participants. Data collection techniques included observation, interviews, and questionnaires, while data analysis was conducted using descriptive quantitative and qualitative approaches. The results showed a significant increase in students’ reading interest and patriotism, with the average reading interest score rising from 76.23 to 85.43 and the patriotism score increasing from 59.15 to 83.85 between Cycle I and II. This improvement was achieved through reading strategies emphasizing active engagement, freedom to choose reading materials, and reflection on story content. In conclusion, the implementation of a reading workshop based on picture books with Indonesian cultural content was effective in fostering reading interest and patriotism, while also enhancing creativity, critical thinking skills, and character awareness among students. The study’s implications suggest that integrating cultural content into literacy activities can serve as an effective learning strategy to improve literacy and character education at the elementary school level.